The impact of CrossFit training on body composition, muscle strength, physiological adaptations, and the development of rebounding and footwork skills in basketball players - Ahmad Hassan (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: CrossFit training can mirror on a physical and technical basketball species improving explosive power, trunk stability, and agility, which are the main performance characteristics of basketball games.